Integrasi Nilai-Nilai Keislaman Pada Peserta Didik Melalui Pembelajaran Pendidikan Agama Islam - Sujiono, Duta Bahagia Rizki; Novianti, Cindy; Wahyudi, Muhammad (STAI Tebing Tinggi Deli, 2024)
The integration of Islamic values among students through Islamic education learning is the main goal of this study. The methodology used is a literature review, often known as library research, which includes the examination of both qualitative and quantitative data from previously published academic publications in addition to conceptual material. In order to analyze the topic under discussion, the researcher's involvement is essential. A number of primary goals are sought in light of the findings and conversations surrounding the incorporation of Islamic values into Islamic education instruction. These include encouraging character development based on Islamic principles like integrity, self-control, accountability, and social duty as well as enhancing students' comprehension of Islamic teachings and how they apply to everyday life. The integration also seeks to improve students' moral and spiritual capacities so they can successfully apply Islamic teachings. It motivates them to submit an application. Educational institutions need effective strategies to ensure the robust integration of Islamic values among students and address challenges that may arise during this process.